Redesigned ITESCM Model: An Academic SCM for the Universities - Pathik, Bishwajit Banik; Habib, Dr. Md. Mamun (International Journal of Supply Chain Management, 2012)
This exploratory research addresses the academic supply chain which consists of educational supply chain and educational management as the major constituents of the ITESCM (Integrated Tertiary Educational Supply Chain Management) model for the universities. The study revealed four main activities; includes education development, education assessment, research development, and research assessment; in the educational management. Four aspects of each main activity, namely Programs Establishment, University Culture, Faculty Capabilities, and Facilities were investigated at three decision levels. The original ITESCM model was developed based on the secondary data, i.e. analysis of the literature, and primary data, i.e. interviews with stakeholders of tertiary academic institutions. Model structures were defined and confirmed by 493 respondents, representing University administrators of leading tertiary educational institutions around the world, faculty and staffs, employers, and graduates. The resulting model was subsequently evaluated for accuracy and validity by multiple linear regression (MLR) analysis and the structural equation modeling (SEM) technique. The redesigned model is the revised form of original ITESCM, that would be easily understandable and research equations are more user friendly for practical field applications. The research model and equations provide a novel approach for prospective investors or current administrators of the tertiary academic institutions to review and appraise their performance toward fulfillment of ultimate goals, i.e. producing high-competent graduates and significant research outcomes for the betterment of the consumer, i.e. the society.